2015
DOI: 10.1140/epjb/e2015-60499-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of earthquake nucleation process represented by the Burridge-Knopoff model

Abstract: Dynamics of earthquake nucleation process is studied on the basis of the one-dimensional BurridgeKnopoff (BK) model obeying the rate-and state-dependent friction (RSF) law. We investigate the properties of the model at each stage of the nucleation process, including the quasi-static initial phase, the unstable acceleration phase and the high-speed rupture phase or a mainshock. Two kinds of nucleation lengths Lsc and Lc are identified and investigated. The nucleation length Lsc and the initial phase exist only … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Shibazaki and Matsu'ura (1993) further found that the accelerating stage from phase-II to phase-III is related to the presence of nucleation phase in the front of the main P wave. Their results are similar to those obtained by Ueda et al (2014Ueda et al ( , 2015 and Kawamura et al (2018). The results of this study and Wang (2017a) only show two stages which are comparable with the phase-II and phase-II stages proposed by Matsu'ura (1992, 1993).…”
Section: Some Comparisons With Other Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…Shibazaki and Matsu'ura (1993) further found that the accelerating stage from phase-II to phase-III is related to the presence of nucleation phase in the front of the main P wave. Their results are similar to those obtained by Ueda et al (2014Ueda et al ( , 2015 and Kawamura et al (2018). The results of this study and Wang (2017a) only show two stages which are comparable with the phase-II and phase-II stages proposed by Matsu'ura (1992, 1993).…”
Section: Some Comparisons With Other Studiessupporting
confidence: 92%
“…Brantut et al (2011) concluded that metamorphic dehydration influences the nucleation of unstable slip and could be an origin for slow-slip events in subduction zones. Ueda et al (2014Ueda et al ( , 2015 and Kawamura et al (2018) pointed out that the nucleation process includes the quasistatic initial phase, the unstable acceleration phase, and the high-speed rupture phase (i.e., a mainshock) and recognized two kinds of nucleation lengths, i.e., L sc and L c which are affected by model parameters, yet not by the earthquake size. The L sc related to the initial phase exists only for a weak frictional instability regime; while the L c associated with the acceleration phase exist for both weak and strong instability regimes.…”
Section: Introductionmentioning
confidence: 99%
“…In the weak frictional instability regime, seismic events generally tend to possess enhanced characteristic features. The magnitude distribution, for example, changes its character depending on whether in the strong or the weak frictional instability regime: the distribution is eminently single-peaked in the weak frictional instability regime whereas tends to be flat in the strong frictional instability regime 13,44 . Large events of the model can be classified into the two categories which we call type-I and II.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the continuum limit where the grid spacing tends to zero, the system is expected to always exhibit a quasi-periodic or a "characteristic" behavior where large earthquakes repeat near-periodically without critical features 35 . Indeed, we recently examined the nature of the nucleation process of the discrete BK model under the RSF law by systematically varying the extent of the discreteness of the model toward the continuum limit, and also by systematically varying various model parameters including the frictional and the elastic parameters 13,44 . It was observed that the model exhibited a quasi-static initial phase in its nucleation process when the frictional instability was weak, i.e., when the normalized frictional-weakening parameter b was less than a critical value b c determined by the elastic-stiffness parameter l as b c = 2l…”
Section: Introductionmentioning
confidence: 99%
“…We note that in some other models, including the Burridge-Knopoff and Olami-Feder-Christensen models, nucleation centres are dynamically generated (e.g. [27,28]). In the present context, however, we introduce an asperity-like behaviour in the construction of the model itself.…”
Section: Modelmentioning
confidence: 94%